Changes in Ghrelin-Related Factors in Gastroesophageal Reflux Disease in Rats - Miwa Nahata; Yayoi Saegusa; Yumi Harada; Naoko Tsuchiya; Tomohisa Hattori; Hiroshi Takeda (Gastroenterology Research and Practice)
To examine gastrointestinal hormone profiles and functional changes in gastroesophageal reflux disease (GERD), blood levels of the orexigenic hormone ghrelin were measured in rats with experimentally induced GERD. During the experiment, plasma acyl ghrelin levels in GERD rats were higher than those in sham-operated rats, although food intake was reduced in GERD rats. Although plasma levels of the appetite-suppressing hormone leptin were significantly decreased in GERD rats, no changes were observed in cholecystokinin levels. Repeated administration of rat ghrelin to GERD rats had no effect on the reduction in body weight or food intake. Therefore, these results suggest that aberrantly increased secretion of peripheral ghrelin and decreased ghrelin responsiveness may occur in GERD rats. Neuropeptide Y and agouti-related peptide mRNA expression in the hypothalamus of GERD rats was significantly increased, whereas proopiomelanocortin mRNA expression was significantly decreased compared to that in sham-operated rats. However, melanin-concentrating hormone (MCH) and prepro-orexin mRNA expression in the hypothalamus of GERD rats was similar to that in sham-operated rats. These results suggest that although GERD rats have higher plasma ghrelin levels, ghrelin signaling in GERD rats may be suppressed due to reduced MCH and/or orexin synthesis in the hypothalamus.